2023
DOI: 10.3390/vaccines11030533
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Estimation of Parental Acceptance of COVID-19 Vaccine for Their Children: A Systematic Review and Meta-Analysis

Abstract: Currently, the best method to well control the spread of COVID-19 without severe mental health problems is to reach herd immunity. Therefore, the vaccination rate of the COVID-19 vaccine is critical. Among the populations, children are the vulnerable ones to get vaccinated; therefore, it is important to assess parents’ and guardians’ willingness to have their children vaccinated. The present systematic review and meta-analysis synthesized evidence to estimate the parents’ acceptance rate of COVID-19 vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 145 publications
4
28
1
Order By: Relevance
“…According to research, 49% of LMIC parents agreed to vaccinate their children and believed that COVID-19 vaccines would be effective in containing the pandemic [ 40 ]. The worldwide parental acceptance rate for COVID-19 vaccines is 58% [ 41 ]. Communication and policies that provide credible information about vaccination [ 42 ], parents’ knowledge and trust about vaccine, cost, accessibility, and government incentives were the factors that encouraged parents to vaccinate their children [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to research, 49% of LMIC parents agreed to vaccinate their children and believed that COVID-19 vaccines would be effective in containing the pandemic [ 40 ]. The worldwide parental acceptance rate for COVID-19 vaccines is 58% [ 41 ]. Communication and policies that provide credible information about vaccination [ 42 ], parents’ knowledge and trust about vaccine, cost, accessibility, and government incentives were the factors that encouraged parents to vaccinate their children [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The worldwide parental acceptance rate for COVID-19 vaccines is 58% [ 41 ]. Communication and policies that provide credible information about vaccination [ 42 ], parents’ knowledge and trust about vaccine, cost, accessibility, and government incentives were the factors that encouraged parents to vaccinate their children [ 41 ]. Vaccine acceptance is not directly proportional to a nation’s income distribution, but rather to an individual’s income and educational qualifications, belief in the vaccine’s ability and safety, and trust in vaccine science [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some potential drivers behind the differences we see in vaccination rates between the age groups may be connected to differing recommendations and offers of vaccination(s) from the Norwegian health authorities. Although the vaccine was made available for both age groups examined in this study during Autumn 2021, only the older group of adolescents [16] , [17] was recommended the vaccine, whereas there was never a general recommendation to vaccinate the young adolescents [12] , [13] , [14] , [15] . Previous studies have shown parents of adolescents to be more willing to vaccinate their children than those of young children [11] , [12] , which might also impact the vaccination rates of the younger group.…”
Section: Discussionmentioning
confidence: 99%
“…The first COVID-19 vaccine in Norway was administered on December 27 th , 2020 and vaccines were offered to defined risk groups for the first part of 2021 before being made available to the broader part of the population. Adolescents with specific, severe underlying diseases aged between 16 and 17 years were recommended the vaccine from February 8 th , 2021 [16] , and adolescents between 12 and 15 years from June 15 th , 2021 [18] . Adolescents without the specified diagnoses and aged 16 to 17 years were recommended vaccines from mid-August, 2021.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to high vaccine hesitancy rates for the HPV vaccine among parents, rates of vaccine hesitancy are high for vaccination overall and may be increasing. 44,45 For instance, Alimoradi et al 46 reviewed 98 peer-reviewed papers from nearly 70 countries in order to understand parental acceptance to the COVID-19 vaccine. Their findings show a low prevalence of such acceptance, with a pooled estimated prevalence of 57% (far lower than what may be necessary to reach herd immunity for COVID-19).…”
Section: Discussionmentioning
confidence: 99%